Experimental Modeling and Treatment Strategies for Peritoneal Carcinomatosis - Aras Emre Canda; Tolga Sever (Turkish Journal of Colorectal Disease)
Peritoneal carcinomatosis (PC), associated with a range of gastrointestinal and gynecological malignancies, represents a significant condition characterized by the dissemination of cancer cells within the peritoneal cavity. The advancement of our comprehension of the pathophysiology and therapeutic strategies for PC hinges on utilizing experimental models. This comprehensive review provides an overview of the current experimental models employed in the examination of PC along with the current treatment strategies. The review comprehensively explores the merits and demerits of each model and their respective contributions to our understanding of peritoneal metastasis. This review will serve as a valuable resource for researchers and clinicians engaged in investigating and managing PC, offering direction for future endeavors to refine experimental modeling and clinical outcomes.